Automated Text-Based Psychological Support to Improve Work-Life Balance and Sleep Quality: A pilot study report of work-from-home workers in Indonesia - Herdiyan Maulana; Faras Hasna Azizah; Lupi Yudhaningrum; Erik Erik; Burhanuddin Tola (ACHSM, 2023)
Background: Work-at-home jobs may raise the risk of mental health concerns as they blur the boundaries between one's job and personal responsibility. This study aimed to develop and test the feasibility of an online psychological intervention using the WhatsAppÓmessaging application. Materials and Method: During the 14-day intervention period, two messages were sent twice a day consisting of positive psychological affirmation aimed at assisting participants (N= 48; 13 males and 35 females) to achieve work-life balance and better sleep quality. The Indonesian-adapted Fisher's work-life balance scale and the sleep disturbance scale were used to measure both constructs. These measures were administered at the beginning and end of the intervention. In addition, we provided participants with brief open-ended questions to check the program's feasibility and acceptance of the intervention. Results: A paired t-test analysis revealed that although there was an increase in work-life balance scores in the post-test compared to the pre-test, the difference was not significant (t (47) = -1.75, p >.05). Nevertheless, individuals' sleep quality scores improved significantly after the intervention (t (47) = − 2.85, p <.05). Discussion: The findings of this study are expected to provide a preliminary argument to further pursue the development of behavioral interventions using online strategies in Indonesia during the pandemic.